Effectiveness Of Family Involvement In Self-Care Management Of Hemodialysis Patients At Bekasi District Hospital - Reza Akmal Wahyudi; Cusmarih Cusmarih (Malahayati Nursing Journal, 2022)
ABSTRACT The incidence of chronic kidney failure in Indonesia is based on data from Riskesdas, (2018), which is 0.38% of the total population of Indonesia of 252,124,458 people, so there are 713 783 people who suffer from chronic kidney failure. Self care management in patients with chronic kidney failure undergoing hemodialysis, family involvement is very important in improving the ability of self- care management of hemodialysis patients. The importance of effective family involvement is needed in escorting patients to carry out self-care management. To determine the effectiveness of family involvement in self-care management of hemodialysis patients at the Bekasi District Hospital.  This type of research uses quantitative analysis, with a cross sectional approach. The sample of this study was the family of hemodialysis patients and hemodialysis patients at the Bekasi District Hospital with 44 respondents. Data analysis was carried out using the Anova test. Univariate results showed that there was a relationship between family involvement and self-care management of hemodialysis patients at the Bekasi District Hospital with p value = 0.000. and the absence of relationship, age, gender, occupation, and duration of hemodialysis. There is a relationship between the effectiveness of family involvement in Self-Care Management of Hemodialysis Patients at the Bekasi District Hospital and hoped that families of hemodialysis patients can be recipients, caring for family members undergoing hemodialysis needs to be improved. because the family assumes that the patient is able to carry out their activities, even though hemodialysis patients experience physical, psychological, social changes in accepting their disease conditions, so they still need help with the involvement of support from the family. Keywords  : Family Involvement, Self-Care Management, Hemodialysis ABSTRAK Angka kejadian gagal ginjal kronis di Indonesia berdasarkan data dari Riskesdas, (2018) yaitu sebesar 0,38 % dari jumlah penduduk Indonesia sebesar 252.124.458 jiwa maka terdapat 713 783 jiwa yang menderita gagal ginjal kronis. Self care management pada pasien gagal ginjal kronik yang menjalani hemodialisa, keterlibatan keluarga sangat penting dalam meningkatkan kemampuan self-care management pasien hemodialisa. Pentingnya efektivitas ketrlibatan keluarga diperlukan dalam mengawal pasien untuk melakukan self-care management. Untuk mengetahui Efektivitas Keterlibatan Keluarga Dalam Self-Care Management Pasien Hemodialisa Di RSUD Kabupaten Bekasi. Jenis penelitian ini menggunakan analisis kuantitatif, dengan pendekatan cross sectional. Sample penelitian ini adalah Keluarga Pasien Hemodialisa dan Pasien Hemodialisa di RSUD Kabupaten Bekasi dengan jumlah responden 44. Analisis data dilakukan dengan menggunakan uji Anova. Hasil Penelitian menunjukan ada hubungan antara keterlibatan keluarga dengan self-care managemen pasien hemodialisa di RSUD kabupaten bekasi nilai p value= 0,000. dan tidak adanya hubungan, usia, jenis kelamin, pekerjaan, dan lama menjalani hemodialisa. Ada hubungan efektivitas keterlibatan keluarga dalam Self-Care Management Pasien Hemodialisa di RSUD Kabupaten Bekasi dan diharapkan keluarga pasien hemodialisa dapat penerima, merawat anggota keluarga yang menjalani hemodialisa perlu ditingkatkan. dikarenakan keluarga beranggapan bahwa pasien mampu melakukan aktifitasnya, padahal pasien hemodialisa mengalami perubahan fisik, psikologis, sosial dalam menerima kondisi penyakitnya, sehingga masih tetap membutuhkan bantuan keterlibatan dukungan dari keluarga. Kata Kunci: Keterlibatan Keluarga, Self-Care Management, Hemodialisa